Peran Bumdes, Optimalisasi Pemanfaatan dan Profesionalisme Pengelolaan Aset Desa terhadap Pendapatan Asli Desa - Nurhidayati, Latifah; Purnama, Hari; Natia Afriany, Arista; Ghifar Zalzalah, Guruh (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
The purpose of this research is to examine the influence of the role of BUMDes, optimizing the utilization of village assets, and the professionalism of managing village assets on the village's original income. This research develops by previous research that was inconsistent by adding the BUMDes role variable. A quantitative approach with primary data is used in this research. The distribution of questionnaires was carried out directly to thirty-seven village goverments in the Bantul Regency to obtain research data. The sampling technique utilized was purposive sampling. One hundred fifty-two respondents consisting of the village head, village secretary, finance section, management section, and BUMDes management, participated in this study. Data analysis used was multiple linear regression techniques using the SPSS Program. The research results showed that the role of BUMDes, optimizing the utilization of village assets, and professionalism of village assets affect the village's original income.